Analysis of School Financial Management in Increasing the Effectiveness of Fund Use at Smpn 15 Mataram - Dimas Rinjani; Resly Febrianti Putri (Penerbit Hellow Pustaka, 2025)
School financial management is crucial for maximizing the quality of education. The success of school administration is determined by effective, efficient, transparent, and accountable fund management. The purpose of this study was to examine how financial management is implemented at SMPN 15 Mataram, with a particular emphasis on improving the efficiency of school expenditures. This research was conducted using a qualitative descriptive approach, and data were collected through observation, interviews, and documentation. The results indicate that SMPN 15 Mataram implements systematic financial management, from planning, implementation, monitoring, and accountability. Transparency and accountability are implemented through the involvement of various parties in the preparation of the School Work Plan (RKAS) and transparent financial reporting. However, problems remain, such as delayed disbursement of School Operational Assistance (BOS) funds and limited human resources for digital financial management. Overall, financial management at SMPN 15 Mataram is considered effective and capable of improving the quality of education.